Social innovation, entrepreneurship, and sport for development and peace - McSweeney, Mitchell; Svensson, Per G.; Hayhurst, Lyndsay; Safai, Parissa (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book examines the ways in which sport for development and peace (SDP) offers an opportunity for entrepreneurship to take place through and within sport, and how innovation in the context of SDP contributes to social and economic value for underrepresented and marginalised groups and individuals. Written by a team of leading international SDP researchers, and featuring the voices of active SDP practitioners, the book examines the ways in which entrepreneurs seek to use sport and/or social innovation in and through sport to achieve their goals of social and economic development. It explores the strategies that SDP organizations and practitioners are utilizing in the current neoliberal moment to not only survive during economic hardship - particularly during the COVID 19 crisis - but also to thrive, drawing on important concepts such as innovation, risk taking, proactiveness and opportunity seeking. It also considers how nongovernmental organizations, companies, governments, and communities are working to tackle development issues in SDP using non-traditional forms of organization and management, such as social enterprise models. Combining cutting-edge research with reflections on best practice in the field, this book is important reading for any advanced student, researcher or practitioner with an interest in the sociology of sport, sport for development, sport management, development studies, social enterprise or innovation.
Keywords: SPORTS & RECREATION / Sociology of Sports; SOCIAL SCIENCE / Third World Development; Sports -- Sociological aspects; Sports -- Economic aspects; Sports and globalization; Peace-building.; Sports and state